Epistaxis, paroxysmal anxiety episodes, and hypertension in a child with SDHB‐associated paraganglioma: A case report. Issue 12 (5th December 2022) - Dorji, Thinley; Verma, Vishesh; Menon, Anil
Abstract: A child presented with anxiety and weight gain which were overlooked until she had epistaxis. She was found to have hypertension secondary to paraganglioma. She was managed with curative surgery involving multidisciplinary care. The tumor removal led to the amelioration of symptoms and marked control of hypertension. Abstract : Evaluation for secondary causes of hypertension is essential especially in children. Pheochromocytomas and paragangliomas are potentially reversible causes of hypertension and can be diagnosed with appropriate biomarkers and imaging.